The impact of administering vitamin D supplements on handgrip strength and performance in the timed-up-and-go test in frail elderly individuals: A meta-analysis involving randomized controlled trials - Pratama, Erdilian; Rizqiansyah , Chrisandi; Firmansah , Wahyu; Soenarti , Sri (Deka in Medicine, 2024)
BACKGROUND: Ongoing debates continue regarding the specific effects of vitamin D intake on the timed-up-and-go test and handgrip strength. OBJECTIVES: To assess the impact of vitamin D supplementation on handgrip strength and performance in the timed-up-and-go test. METHODS: Between May and June of 2023, a systematic review and meta-analysis were undertaken to assess the effects of vitamin D intake on handgrip strength and performance in the timed-up-and-go test. A comprehensive search was performed on Google Scholar, Web of Science, and PubMed to search for relevant articles published until June 2023. The analysis exclusively incorporated randomized controlled trials (RCTs) available in English publications, with a specific emphasis on evaluating the impact of vitamin D supplementation on both handgrip strength and performance in the timed-up-and-go test. Inverse variant meta-analysis was employed to evaluate the impact of vitamin D intake on the timed-up-and-go test and handgrip strength. RESULTS: A total of 21 appropriate studies were incorporated into the systematic review. Our findings revealed a favorable impact of vitamin D administration on enhancing performance in the timed-up-and-go test. Conversely, we could not ascertain any advantageous effects of vitamin D intake on handgrip strength. Despite the notable enhancement observed in the timed-up-and-go test, our analysis did not yield statistically significant evidence supporting the impact of vitamin D intake on handgrip strength based on the included studies. CONCLUSION: Our study findings reveal that vitamin D is an essential component in improving the timed-up-and-go test.